Raw milk quality - milk flavor - Roberts, H. A. (Kansas Agricultural Experiment Station, 2011)
Flavor control in market milk begins on the farm and continues through the processing plant and into the home of the consumer. Flavor control is directly or indirectly related to the health of the cow, the feeding of the cow, the cleaning and sanitizing of utensils, the cooling of the milk, transportation to the processing plant, and all the steps in processing and distribution of the milk. Consumers judge the quality of milk largely by taste and appearance. Therefore, it is important that each load of milk be checked for off-flavors before it is loaded on the tank truck and again when it is received at the processing plant. Learning to recognize and distinguish certain characteristics of each possible offflavor that may be present in milk is important. This will help the dairyman and the fieldman in tracing the source of any off-flavors in milk and assist in reducing or eliminating the cause. At the end of this article, you will find a chart explaining some of the milk flavor defects, possible causes, and preventions. Cut this page out and place it near your milk tank for reference.
Keywords: Dairy; Dairy products; Milk quality; Milk flavor